The novel use of lauromacrogol: A respective study of ultrasound‐guided sclerosant injection for cesarean scar pregnancy. Issue 1 (9th November 2021) - Zhu, Linling; Gao, Jiansong; Yang, Xinyun; Qian, Liang; Wang, Yanjing; Zhang, Hongyun; Chen, Beibei; Li, Dingheng
Abstract: Aim: To introduce the novel use of lauromacrogol for cesarean scar pregnancy (CSP), and to compare the clinical efficacy and safety of curettage combined with ultrasound‐guided sclerosant injection (USI) and curettage following uterine artery embolization (UAE) in the treatment of CSP. Methods: CSP patients undergoing curettage combined with USI ( n  = 72) from December 2014 to May 2020 were compared to patient with curettage following UAE ( n  = 72).The basic clinical findings and clinical outcomes were reviewed between the two groups. Results: For USI group, 69 patients underwent successful treatment (95.8% success rate), while the number of cured patients for the UAE group was 70 (97.2% success rate). Differences between USI group and UAE group in intraoperative blood loss (10.0 [10.0–20.0] vs. 10.0 [10.0–20.0] mL) and time for serum β human chorionic gonadotropin (β‐hCG) to reduce to normal (28.0 [21.0–40.0] vs. 28.0 [21.0–35.0] days) were not statistically significant. The hospital stay for USI group was significantly shorter than that for UAE group (4.0 [4.0–6.0] vs. 6.0 [5.0–7.0] days, respectively). Statistically significant decreases were noted in hospitalization expenses and adverse events in USI group, compared to UAE group. There was no difference in live birth rate between the two groups with fertility intentions during the follow‐up. Conclusion: For treatment of CSP, curettage combined with USI yielded clinical results comparable to those of curettage following UAE. Curettage combined with USI was associated with lower hospitalization expenses, shorter hospital stay and less complications, and it merited an effective and safe treatment for CSP.